2015
DOI: 10.1248/bpb.b15-00053
|View full text |Cite
|
Sign up to set email alerts
|

A Compound Inhibits Biofilm Formation of <i>Staphylococcus aureus</i> from <i>Streptomyces</i>

Abstract: Biofilm is one virulence factor of bacteria. It contributes not only to bacterial adherence to many kinds of infection-establishing surfaces, but also to bacterial resistance against antimicrobial agents and antiseptic agents. Thus, inhibitors of bacterial biofilm formation should be useful in the prevention of infections. We found that a culture of Streptomyces sp. strain MC11024 showed inhibitory activity on biofilm formation by Staphylococcus aureus and isolated streptorubin B as an inhibitor of this format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…; Suzuki et al . ). However, there are few documents about S. epidermidis biofilm inhibitors from Actinomycete .…”
Section: Introductionmentioning
confidence: 97%
“…; Suzuki et al . ). However, there are few documents about S. epidermidis biofilm inhibitors from Actinomycete .…”
Section: Introductionmentioning
confidence: 97%
“…; Xie et al ). Consequently, inhibitors of S. epidermidis biofilm formation are good candidates for anti‐infectious agents, as such agents should work for not only preventing attachment to surfaces but also attenuating resistance to antibiotic agents (Suzuki et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of prodigiosin required to inhibit biofilm formation of P. aeruginosa was within the range of 100–500 μM, which is at least five times higher than the reported concentrations required to induce apoptosis in human cancer cell lines (da Silva Melo et al, 2000 ; Montaner et al, 2000 ; Montaner and Perez-Tomas, 2001 ) and larger than the concentration of Streptorubin B to inhibit biofilm formation (Suzuki et al, 2015 ). Prodigiosin induces apoptotic effect in cancer cell lines through regulation of apoptopic and anti-apoptotic genes (Hassankhani et al, 2014 ), while the prodigiosin mediated biofilm inhibition has shown to rely on the production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 87%
“…), has shown to be a very potent inhibitor of biofilm formation of S. aureus . However, the exact biofilm inhibitory mechanism of Streptorubin B remains unknown (Suzuki et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%